Reconfigurable Intelligent Surfaces Enabling Future Wireless Communication - Soto-Gomez, J; Adasme-Soto, P; Ayub-, M (Institute of Electrical and Electronics Engineers Inc., 2021)
Reconfigurable Intelligent Surface (RIS) has been considered as a promising technology that provides ultra-high speed for 5G beyond (5GB) and future 6G wireless communication systems. An RIS has boosted the concept of Smart Radio Environment (SRE) to enable Massive Connectivity with Massive MIMO System. RIS and Massive MIMO are both key enablers at the infrastructural level while millimeter wave (mm-Wave) and Tera Hertz (THz) communication are the key enablers at spectrum level for 5G and 6G. In this article, we discuss some potential candidate technologies and applications using mm-Wave Massive MIMO that can be well equipped with RIS in order to play a vital role in future wireless communication. The applications include Unnamed Aerial Vehicle and Visible Light Communications (VLC). In particular, we discuss and provide insights for VLC technology using RIS. As far as we know, these novel technologies have not been discussed and analyzed in a joint manner so far. © 2021 IEEE.